건설용 리프트의 운행정보 및 고장데이터 분석을 통한 주요 부품별 점검주기 산출 연구 - 소지윤; 배재훈; 한충희; 이준복; Soh, Jiyune; Bae, Jaehoon; Han, Choonghee; Lee, Junbok (한국건설관리학회 논문집, 16(3), 2015)
One of recent concerns for super-tall buildings is how to manage hoisting plans and equipment efficiently. Disasters are frequently occurred in relation to electromotive hoists and cranes which are commonly used in construction sites. For construction lifts, particularly, it is highly important to conduct regular inspections or prepare against breakdown in terms of safety. However, unfortunately the reality is that regular inspections are only flatly conducted according to operating hours only. A lift, whose life span is subject to the complicated considerations such as operating hours, loading condition, and the like of each component, is far too invalid as a means of maintenance. As a way to resolve this problem and improve its convenience and safety for users, this study intends to calculate individual inspection interval for the main components of lifts by measuring their actual operating hours with sensing technology and analyzing their historical data. The findings of study include calculation of inspection intervals for the main components of lifts and classification of components to check by the actual operating hours of lift (40, 90, 130, 400 hours), which are drawn up into tables. This will make an opportunity to suggest efficient maintenance measures by enabling prevention of safety accidents and enhancement of safety for workers. Also, it will lead to increasing productivity of works by eliminating sources of delaying the term due to the breakdown of lifts. 최근 초고층 건축물의 증가로 그에 따른 양중계획 및 양중장비의 효율적 관리에 대한 관심이 증대되고 있다. 건설 현장에서 폭넓게 사용되고 있는 전동 호이스트, 크레인 등과 관련된 재해사고가 빈번히 발생하고 있다. 특히 건설용 리프트는 안전 측면에서 정기점검이나 고장에 대비하는 것이 대단히 중요하나 사용시간에 따른 일률적인 정기검사를 수행하고 있는 실정이다. 리프트는 개별 부품의 사용시간 및 부하조건 등에 따라 그 수명이 달라질 수 있기 때문에 실효성이 매우 떨어지는 유지관리 방법이라고 할 수 있다. 본 연구에서는 이러한 문제점을 개선하고 사용자 편의성과 안전성을 증대시키기 위한 방안으로써 센싱 기술을 활용하여 리프트의 실제 사용시간을 측정하고 그에 따른 고장데이터를 분석하여 리프트의 주요 부품들에 대한 개별 점검주기를 산출하는 것을 목적으로 하였다. 연구의 결과물로 리프트의 주요 부품에 대한 점검주기를 산출하고, 리프트 실 사용시간 40시간, 90시간, 130시간, 400시간으로 나누어 그에 따른 점검 부품들을 구분하여 표로 작성하였다. 이를 통해 안전사고를 미연에 방지하고 작업자의 안전성을 향상시켜 효율적인 유지관리 방안을 제시할 수 있을 것으로 사료된다. 또한 리프트 고장으로 인한 공기지연 요소를 사전에 제거하여 공사의 생산성을 증대시킬 수 있을 것이다.